Exploring The Roots Of The Failure Of Islamic Religious Education In Achieving Its Final Goals - Uswatun Chasanah; Ida Zahara Adibah; Sirojul Baehaqi; Mowafg Masuwd; Mohieddin Masoud (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study aims to examine in depth the roots of the failure of Islamic Religious Education (PAI) in achieving its ultimate goal, namely to form students who are faithful, pious, and have noble character in everyday life. Through a qualitative approach with content analysis methods and comprehensive literature studies, this study identifies fundamental factors that cause the gap between the ideals and the reality of PAI implementation in Indonesia. The results of the study indicate that there are several main factors for PAI failure, including: problems with the curriculum that is not contextual, learning methods that tend to be indoctrinative, lack of teacher competence, limited infrastructure, disparities in education policies, the influence of globalization and digitalization, and minimal collaboration between three educational centers. The implication of this study is the need for a comprehensive reformulation and revitalization of the PAI system that involves all stakeholders, by considering philosophical, sociological, psychological, and technical pedagogical aspects to realize the ultimate goal of PAI in forming perfect human beings who reflect Islamic values ​​in life.